"Throw the Money in the Air": Ideological Rejoinder in Olamide's Omo Abule Sowo. Issue 2 (3rd July 2021) - Sunday, Adesina B.
Abstract: This article discusses an analysis that examined how Olamide Adedeji (whose stage name is Olamide), a popular Nigerian hip-hop artiste, uses his album Omo Abule Sowo ( Abule Sowo means someone who can literally make money out of anything) as a rejoinder to people's views about him. The objectives of the analysis were to determine the ideologies encapsulated on the album, describe the pragmatic acts, and identify the devices deployed in achieving his goal. Norman Fairclough's approach to critical discourse analysis (CDA), complemented by Jacob Mey's pragmatic acts theory, served as the theoretical framework. The album was purposively selected because of its thematic relevance. The descriptive research design was adopted. The song text was subjected to pragmatic analysis which revealed that Olamide utilises hedonistic and supremacist ideologies; he deploys the practs of asserting, informing, mocking, warning and threatening; he attacks his unnamed detractors pungently while stressing his own invincibility; he tactically utilises similes, metaphors, allusion and code alternation; he deploys traditional and modern imagery to cater for old and young listeners; he uses mainly call-and-response in presenting the song; and he deploys the members' resources of the Yoruba artistically to ward off attack and instil fear in his enemies.